Road infrastructure and intra-community trade in the Central African Economic and Monetary Community (International Journal of Scientific Research and Management (IJSRM), 2022)
We examine the contribution of domestic and interstates road infrastructures to trade flow between member countries of the Central African Economic and Monetary Community (CEMAC). Theories of international economics as well as those of the new economic geography suggest a positive contribution of both road infrastructures to intraregional trade. A gravity model of international trade is estimated to evaluate this theoretical prediction in the CEMAC zone. Results confirm a positive contribution of interstate road infrastructure to intra-Community trade, but show no evidence of a positive contribution of domestic road infrastructure to intra- CEMAC trade.